Is there a Relationship between Bone Morphology and Injured Ligament on Imaging Studies and Laxity on Ankle Stress Radiographs? - Lee, S. Y.; Kwon, S.-S.; Park, M. S.; Chung, M. K.; Kim, K. B.; Koo, S.; Lee, K. M. (International Journal of Sports Medicine, 2016)
This study aimed to investigate the relationship between bone morphology and injured ligaments on imaging studies and laxity on ankle stress radiographs in patients with lateral ankle instability. In total, 115 patients who had undergone ankle MRI, ankle radiography, and stress radiography were included. Distal tibial articular surface angle, bimalleolar tilt, medial and lateral malleolar relative length, medial malleolar slip angle, anterior inclination of the tibia, and fibular position were measured on ankle radiographs. Tibiotalar tilt angle and anterior translation of the talus were measured on ankle stress radiographs. Degree of ligament injury was evaluated on ankle MRIs. Multiple regression analysis was performed using the following independent variables: age, sex, and factors significantly associated with ankle stress view on univariate linear regression analysis. Age (p=0.041), sex (p=0.014), degree of anterior talofibular ligament injury (p<0.001), and bimalleolar tilt (p=0.016) were correlated with tibiotalar tilt angle. Fibular position and degree of posterior talofibular ligament injury were factors significantly related to anterior translation of the talus. Differences in patient characteristics might predispose ankle stress radiograph results. Comparison of both ankles on stress radiographs is superior to applying fixed numerical values to the injured side in order to reduce the influence of patient factors.
Keywords: ankle stress radiographs; lateral ankle instability; anterior talofibular ligament; bimalleolar tilt; tibiotalar tilt angle; fibular position